Az igazságosság mint indok a Kúria 21. századi magánjogi gyakorlatában - Benke, József (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
After a brief overview of the ancient and medieval history of the notion of justice in philosophy, and some anthropological remarks, the paper examines the precedent decisions of the supreme judicial forum of Hungary (Kúria) delivered over the past 10 years in the field of private law with respect to whether the legal reasoning of the judgments contain a manifest reference to the notions of “just” or “justice”. As a result of this research, we find that the judgments, without any further reference, and apart from the modern notions of substantive and procedural justice, are based mainly on the concepts of corrective (rectificatory) justice and on that of distributive justice as well, as if by instinct following the teachings of Aristotle and Thomas Aquinas.